Risk and Insurance in Village India - Townsend, Robert M. (Econometrica, 1994)
The objective of the Institute for Policy Reform is to enhance the foundation for broad based economic growth in developing countries.Through its research, education and training activities the Institute encourages active participation in the dialogue on policy reform, focusing on changes that stimulate and sustain economic development.At the core of these activities is the search for creative ideas that can be used to design constitutional, institutional and policy reforms.Research fellows and policy practitioners are engaged by IPR to expand the analytical core of the reform process.This includes all elements of comprehensive and customized reforms packages, recognizing cultural, political, economic and environmental elements as crucial dimensions of societies.